Nilai Kosmologi pada Tata Spasial Permukiman Desa Kapencar, Lereng Gunung Sindoro, Wonosobo - VG Sri Rejeki; Nindyo Soewarno; Sudaryono Sudaryono; T. Yoyok Wahyu Subroto (Forum Teknik, 2010)
The Kapencar Village, as one of villages on the slope of Sumbing Mountain, hascosmological concept of spatial setting. The phenomenological research, was done by theresearcher as own instrument, explored for finding the spatial cosmological value in theKapencar villages. Some results of the research are:1) The Kapencar Village as the Glondongvilage, expresed the mon-copat concept, with the Kapencar village as the centre. 2) keblatwetan as a cosmological concept. Wetan orientation as a symbol of the start of living or thevery previous time of people living. Two cosmological concepts of spatial setting expresed theKapencar Village has the grand cosmologycal concept in people lining, there is keblat papatkalimo pancer (four orientations and the centre as the fifth oerintation).Kata kunci : Cosmology; the slope of the mountain settlement; spatial setting